Impaired dimerization of von Willebrand factor subunit due to mutation A2801D in the CK domain results in a recessive type 2A subtype IID von Willebrand disease - Hommais, Antoine; Stépanian, Alain; Fressinaud, Edith; Mazurier, Claudine; Pouymayou, Katia; Meyer, Dominique; Girma, Jean-Pierre; Ribba, Anne-Sophie (Thrombosis and Haemostasis, 2006)
The CK domain of von Willebrand factor (VWF) is involved in the dimerization of the protein.We identified the homozygous substitution A2801D of the CK domain in two siblings. Patients had low levels of VWF in plasma, abnormal ristocetin-induced binding to platelets and abnormal multimeric pattern witha lack of high molecular weight (HMW) forms and the presence of intervening bands between normal multimers. Accordingly, they were classified in type 2A, subtype IID, von Willebrand disease (VWD). Both asymptomatic parents carried the mutation at the heterozygous state.Their plasmaVWF exhibited the full range of multimers found in normal plasma.When analyzed by high resolution gel electrophoresis, very faint bands corresponding to the position of intervening bands of the propositus can be observed. The mutated recombinant (r)VWF-D2801, the hybrid rVWF-A/D2801 and the mutated C-terminal VWF fragment rSPII-D2801 were expressed in COS-7 cells. rVWF-D2801 showed an abnormal multimeric distribution similar to that of the propositus’VWF with intervening bands and a lack of HMW species. rVWF-A/D2801 exhibited the full range of multimers and the aberrant sized forms observed both in propositus’VWF and in rVWF-D2801. rSPII-WT assembled correctly into a dimer of 220 kDa. rSPII-D2801 appeared as a mixture of monomeric and dimeric forms which may be related to the abnormal multimeric pattern of the propositus and both mutated rVWF. We concluded that mutation A2801D disturbs the folding of the CK domain, which may result in a mixture of monomers and dimers of VWF. Multimers containing either an odd or even number of mature subunits are produced, and the presence of monomers appears to limit the degree of multimerization. In the heterozygousVWF,the presence of normal dimers improves the multimerization process. In conclusion, the mutation A2801D appears to be responsible fora recessive type 2A, subtype IID, VWD.
Keywords: von Willebrand factor; von Willebrand disease; type 2A VWF; dimerization; CK domain